The bioecology of Dacus ciliatus (Diptera: Tephritidae) in a butternut squash production system within the Western Cape of South Africa - Van Rooyen, Rigardt Johan (Stellenbosch : Stellenbosch University, 2026)
Thesis (MScAgric)--Stellenbosch University, 2026.